Deep rooting in-situ expansion of mtDNA Haplogroup R8 in South Asia. - Kumarasamy Thangaraj (Public Library of Science (PLoS), 2009)
Background The phylogeny of the indigenous Indian-specific mitochondrial DNA (mtDNA) haplogroups have been determined and refined in previous reports. Similar to mtDNA superhaplogroups M and N, a profusion of reports are also available for superhaplogroup R. However, there is a dearth of information on South Asian subhaplogroups in particular, including R8. Therefore, we ought to access the genealogy and pre-historic expansion of haplogroup R8 which is considered one of the autochthonous lineages of South Asia. Methodology/principal findings Upon screening the mtDNA of 5,836 individuals belonging to 104 distinct ethnic populations of the Indian subcontinent, we found 54 individuals with the HVS-I motif that defines the R8 haplogroup. Complete mtDNA sequencing of these 54 individuals revealed two deep-rooted subclades: R8a and R8b. Furthermore, these subclades split into several fine subclades. An isofrequency contour map detected the highest frequency of R8 in the state of Orissa. Spearman's rank correlation analysis suggests significant correlation of R8 occurrence with geography. Conclusions/significance The coalescent age of newly-characterized subclades of R8, R8a (15.4+/-7.2 Kya) and R8b (25.7+/-10.2 Kya) indicates that the initial maternal colonization of this haplogroup occurred during the middle and upper Paleolithic period, roughly around 40 to 45 Kya. These results signify that the southern part of Orissa currently inhabited by Munda speakers is likely the origin of these autochthonous maternal deep-rooted haplogroups. Our high-resolution study on the genesis of R8 haplogroup provides ample evidence of its deep-rooted ancestry among the Orissa (Austro-Asiatic) tribes.